Anaerobic digestion of heat treated sludge liquor by pilot scale mesophilic EGSB reactor - Jing, Zhao; Wei, Qiao; Wei, Wang; Fang, Gao; Zheng, Xiao (International Journal of Agricultural and Biological Engineering, 2016)
Biogas recovery from heat treated sludge liquor was tested by a 4 m3 mesophilic expanded granular sludge bed (EGSB) reactor within 206 days. Before pilot experiment, the heat pretreatment effects on hydrolysis and biogas production potential on three sludges from different wastewater plants were evaluated using bench test. One of these sludges was used in the subsequent pilot heat treatment and EGSB reactor. The biogas conversion potential of this sludge filtrate was 79%. Seeded with granular sludge, the EGSB reactor could be quickly activated and adapted to the new filtrate substrate. The EGSB influent COD was 20.0-35.0 g/L, and the effluent COD was lower than 10.0 g/L. The COD removal rate was 60%-70% at an organic loading rate (OLR) of 10.0 kg COD/(m3•d). The fresh supernatant with low pH resulted in the high biogas production in EGSB. The effluent with high nitrogen and phosphor should be considered for further treatment.Keywords: anaerobic digestion, sludge, biogas, heat treatment, EGSB reactor, pilot scaleDOI: 10.3965/j.ijabe.20160903.2371Citation: Zhao J, Qiao W, Wang W, Gao F, Xiao Z. Anaerobic digestion of heat treated sludge liquor by pilot scale mesophilic EGSB reactor. Int J Agric & Biol Eng, 2016; 9(3): 146－153.